(3COH GdOfjG hGdOjfs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s ((3YeQGf Hf eMeO Hf CHj GdfhQ GdZQjGfi GdeZQHi s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdWhd hGdBdGA CeG HYO aEf TQa GdeWdhH HTQa fJGFLg hCYXe GdCehQ NWQkG hbOQkG eG ESJbGe Hg UdGM GdOjf hGdOfjG hbO JhNjJ HgPG GdcJGH GdEQTGQI Edi BOGHgeG s
(3BNQgG (B:s
(3agPG CjgG dGYGbd faSc HEfcGQ YjhHc CYffG Gddg hEjGc hgh MSHfG hfYe Gdhcjd s
(3HYV cdeGJgG HGdMeQI hYdjgG JUMjMGJs
(3YdjgG Jedc HGSe eMeO Hf MLQ GdTGaYi Gdeci GdCfUGQi GdLfjOis
(3SfI (B1067(3g`s
(3hJedc BNQ HGSe YjO QhSi Hf Ybjd GdLaQi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdadSaI hGdefWbs